The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/2015jd023788
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution satellite‐gauge merged precipitation climatologies of the Tropical Andes

Abstract: Satellite precipitation products are becoming increasingly useful to complement rain gauge networks in regions where these are too sparse to capture spatial precipitation patterns, such as in the Tropical Andes. The Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar (TPR) was active for 17 years (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) and has generated one of the longest single-sensor, high-resolution, and high-accuracy rainfall records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 70 publications
(117 reference statements)
3
69
0
4
Order By: Relevance
“…This is consistent with [32], where the climatological maps showed that western Ecuador is underestimated by TRMM. This behavior was improved by the step 2 methods, where P RKT and P RKTC showed to be better products than those which did not apply residual kriging correction, reducing both RMSE and PBI AS.…”
Section: Results Summary and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with [32], where the climatological maps showed that western Ecuador is underestimated by TRMM. This behavior was improved by the step 2 methods, where P RKT and P RKTC showed to be better products than those which did not apply residual kriging correction, reducing both RMSE and PBI AS.…”
Section: Results Summary and Discussionsupporting
confidence: 80%
“…The results revealed that the performance of the method is related to the density of the station network. Furthermore, NDVI was used as an auxiliary variable in [32], where a very large area of almost 4 countries (Colombia, Ecuador, Brazil and Peru) was covered, where TRMM was merged with 273 in situ stations. However, climatological maps were generated, making it still necessary to treat time series at finer temporal scales over the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Mean annual precipitation of all rain gauges in the region is 713 mm, while the maximum reported area-average daily rainfall in the study period is 540 mm. Precipitation patterns are controlled by the interaction of synoptic-scale atmospheric currents and the complex Andean topography (Manz et al 2016). The Pacific coastline is arid and experiences precipitation less than 100 mm yr 21 as a result of the cold von Humboldt current (Manz et al 2016), which increases toward the Andes mountainous range because of strong topographic gradients that result in pronounced orographic effects (Espinoza et al 2015;Espinoza Villar et al 2009;Bookhagen and Strecker 2008).…”
Section: A Study Domains and Rain Gauge Datasetsmentioning
confidence: 99%
“…Several other studies (e.g., [13,45,46]) showed that, during the daytime, satellite-based rainfall retrievals benefit from additionally considering VIS channels. However, when taking VIS channels into account, two separate algorithms need to be used for day-and nighttime with the nighttime algorithm exhibiting lower skill.…”
Section: Discussionmentioning
confidence: 99%
“…Often, different data sources are combined to enhance the QPE accuracy, e.g., ground-based radar and gauges (e.g., [9,10]), ground-based radar and satellite radiometer (e.g., [11]), satellite radiometer and gauges (e.g. [7,12]), spaceborne radar and gauges (e.g., [13]), spaceborne radar and satellite radiometer (e.g., [14,15]), or spaceborne radar, satellite radiometer, and gauges (e.g., [16]). Each precipitation measurement instrument has its specific set of strengths and limitations.…”
Section: Introductionmentioning
confidence: 99%